Roll Away the Reel World : James Joyce and Cinema - McCourt, John, 1965- (Book collections on Project MUSE., 2010)
This title focuses on Joyce's interest and involvement in early modern cinema and his subsequent thematic and formal borrowing for this genre. It looks at cinema's interest in Joyce as seen in important film versions of his work.